2006
DOI: 10.1074/jbc.m511155200
|View full text |Cite
|
Sign up to set email alerts
|

Solution Structure of Human Peptidyl Prolyl Isomerase-like Protein 1 and Insights into Its Interaction with SKIP

Abstract: The human PPIL1 (peptidyl prolyl isomerase-like protein 1) is a specific component of human 35 S U5 small nuclear ribonucleoprotein particle and 45 S activated spliceosome. It is recruited by SKIP, another essential component of 45 S activated spliceosome, into spliceosome just before the catalytic step 1. It stably associates with SKIP, which also exists in 35 S and activated spliceosome as a nuclear matrix protein. We report here the solution structure of PPIL1 determined by NMR spectroscopy. The structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
61
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 35 publications
(35 reference statements)
4
61
0
Order By: Relevance
“…The N-proximal 180 amino acids of SnwA (ortholog of human SKIP) interact with CypE (ortholog of human PPIL1) in Dictyostelium discoideum (18). Xu et al (17) confirmed that the N-terminal of SKIP (residues 59 -129, SKIPN) is sufficient to associate with PPIL1. Nevertheless, how they bind and the structural basis of their binding are still unknown.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…The N-proximal 180 amino acids of SnwA (ortholog of human SKIP) interact with CypE (ortholog of human PPIL1) in Dictyostelium discoideum (18). Xu et al (17) confirmed that the N-terminal of SKIP (residues 59 -129, SKIPN) is sufficient to associate with PPIL1. Nevertheless, how they bind and the structural basis of their binding are still unknown.…”
mentioning
confidence: 61%
“…PPIL1 (166 residues) belongs to a novel subfamily of cyclophilin, which contains a single domain (PPIase domain) and has a SKIP-binding region and a cyclosporin A (inhibitor of peptidylprolyl isomerase)-binding region (17). SKIP recruits PPIL1 into the spliceosome.…”
mentioning
confidence: 99%
“…At the HIV-1 promoter, SKIP recruits c-Myc and also interacts with the MLL1:Menin histone methyltransferase to promote H3K4 methylation (Brè s et al 2009). Previous studies found that SKIP also binds U2AF35 , the PPIL1 peptidyl-prolyl isomerase Xu et al 2006), and the DExH RNA helicase Prp22 (Gahura et al 2009), which helps release mRNA from the spliceosome (Schwer 2008). SKIP is required for cell survival and stress resistance in plants (Hou et al 2009), and depletion of human SKIP or hPrp22 results in mitotic spindle defects and accumulation in prometaphase (Kittler et al 2004(Kittler et al , 2005, indicating an important role in cell cycle progression.…”
mentioning
confidence: 99%
“…Cis-trans isomerization of proline-linked peptide bonds is a rate-limiting step in protein folding, catalyzed by peptidylprolyl isomerases (PPIs) including cyclophilin A (CyPA) and FK506-binding protein (FKBP) (30,31). PPI inhibition will likely affect protein levels and potentially reveal the mechanism involved in protein (mis)folding of PPI substrates.…”
Section: Gdca (mentioning
confidence: 99%